2020
DOI: 10.52571/ptq.v17.n36.2020.472_periodico36_pgs_457_475.pdf
|View full text |Cite
|
Sign up to set email alerts
|

COMPARATIVE HISTOCHEMICAL AND HISTOMORPHOMETRICAL STUDY OF ESOPHAGUS STRUCTURES IN SHEEP (Ovis aries) AND RABBITS (Oryctolagus Cuniculus)

Abstract: Evolution between animals causes many changes so that it can adapt to its environments. Each species has unique features that help them survive and can consume different types of food. Sheep and rabbits are economically important animals and used in many aspects of veterinary medicine.This study aimed to compare the histomorphometric and histochemical features of the esophagus of twenty sheep (n = 10) and rabbit (n = 10) adult males. The samples were collected from slaughterhouse and market Misan and were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In rabbits, sheep, and goats, the muscularis mucosa contains an interrupted single layer of smooth muscles [ 28 , 29 ], thinly dispersed become thicker in the thoracic region in the Grey Mongoose esophagus [ 25 ], and prominent along the entire length of the esophagus of agouti [ 26 ] and camel [ 6 ]. Our findings revealed that the muscularis mucosa as continuous smooth muscle fibers in the abdominal part coincided with Hussein et al [ 6 ], who referred for continued muscularis mucosae in the camel‘s caudal part of the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…In rabbits, sheep, and goats, the muscularis mucosa contains an interrupted single layer of smooth muscles [ 28 , 29 ], thinly dispersed become thicker in the thoracic region in the Grey Mongoose esophagus [ 25 ], and prominent along the entire length of the esophagus of agouti [ 26 ] and camel [ 6 ]. Our findings revealed that the muscularis mucosa as continuous smooth muscle fibers in the abdominal part coincided with Hussein et al [ 6 ], who referred for continued muscularis mucosae in the camel‘s caudal part of the esophagus.…”
Section: Discussionmentioning
confidence: 99%